2022
DOI: 10.15408/ajis.v22i1.23687
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Fatwa and Da'wah Acceptance in New Media: How Technology Affects Religious Message by Female Ulama

Abstract: Through religious activities in cyberspace, new media has become one of the enabling reasons for the emergence of female ulama. It has created a channel for them to exhibit their identity and compete as religious preachers. Numerous Islamic studies organizations and societies have developed on social media, along with religious leaders who use the platform to disseminate Islamic learning activities across various social media channels, increasingly highlighting the signals of religious populism. This study emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The da'wah scene and its relationship with gender is a fertile ground for further research. As quoted by Imam Subchi in his research "Integration of Islamic da'wah and It: Phenomena of Quran interpretation in Indonesian online Islamic media" suggests that the digital space has silenced women's voices to seek neutrality in the religious space, especially fatwas that glorify men (Subchi et al, 2022).…”
Section: Study Of Da'wah Text On Muslimid: the Perspective Of Sara Mi...mentioning
confidence: 99%
“…The da'wah scene and its relationship with gender is a fertile ground for further research. As quoted by Imam Subchi in his research "Integration of Islamic da'wah and It: Phenomena of Quran interpretation in Indonesian online Islamic media" suggests that the digital space has silenced women's voices to seek neutrality in the religious space, especially fatwas that glorify men (Subchi et al, 2022).…”
Section: Study Of Da'wah Text On Muslimid: the Perspective Of Sara Mi...mentioning
confidence: 99%
“…The use of social influence as a stimulant of electronic library usage behaviours has been validated by Kunst et al (2022) as well. Many studies have furthered our understanding of social influence in behavioural intention research over the years, which has led to a more pluralistic understanding of social influence (Subchi et al, 2022;Zheng et al, 2022). A study conducted by Veenstra and Lodder (2022), for instance, found that group-level determinants such as group norms and identity play an important role in influencing behavioural intention at the group level.…”
Section: The Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%